Harmonizing Visuals: The Synergy of Compositing and Colour Grading in FilmProduction"- Harmonisasi Visual: Sinergi Compositing dan Color Grading dalam FilmProduksi - Asti Haningtyas, S.I.Kom, M.I.Kom, Asti Haningtyas, S.I.Kom, M.I.Kom (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2023)
This paper is discussing the important role played by compositing and color grading in the film industry, which contributes greatly to the visual appearance of films. Compositing is the process of combining various visual elements such as green screen, special effects, and image layers to create a true-to-life scene. This process allows for the creation of stunning visual effects such as explosions, monsters, or fantastic landscapes. The methodological approach carried out in this study is called literature research. The result of this writing is that adjusting the color, contrast, and lighting in the film to achieve the desired mood and feel can be done through color grading and lighting. This can change the audience's feelings towards the scene from a dark and mysterious one to a bright and pleasant one. Both functions together to produce balanced and harmonious movie images. Color grading ensures the overall look, while compositing creates scenes with strong visual elements.